Pigeon tick Argas reflexus (Ixodida: Argasidae) in south-eastern Poland – biological features and clinical symptoms - Buczek, Alicja; Bartosik, Katarzyna; Szymańska, Jolanta; Buczek, Sebastian (Polish Journal of Public Health, 2011)
The paper describes a new site of the pigeon tick (Argas reflexus) at Kędzierzyn Koźle (south-western Poland) and biological features of the species facilitating its survival in residential buildings, as well as the consequences of its parasitizing on humans.As this tick species is widespread and important from medical point of view, it is necessary to disseminate knowledge on pigeon ticks and on prophylactic measures, and also to organize integrated actions of sanitary services, disinfection teams and administrators of buildings in order to reduce the number of pigeon ticks in urban areas.